2011
DOI: 10.5713/ajas.2011.11060
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritive Value of Live Yeast Culture (Saccharomyces cerevisiae) and Its Effect on Milk Yield, Milk Composition and Some Blood Parameters of Dairy Cows

Abstract: This study was conducted to determine the nutritive value of live yeast culture (RumiSacc, Saccharomyces cerevisiae) and to investigate its effects on milk yield, milk composition and some blood parameters in lactating cows. Six multiparous Holstein cows were allocated to two groups of three cows and assigned randomly to one of two diets in a cross-over experiment. Daily 50 g RumiSacc was top dressed at the p.m. feeding for the treatment group. RumiSacc supplied a high protein and energy with high organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
7
27
0
Order By: Relevance
“…Blood chemistry results and some hematological parameter results of present study had parallel with the of results Özsoy et al [7] that plasma cholesterol and triglyceride concentrations were not altered by yeast culture supplementation on goats and Yalçın et al [1] on dairy cows. On the other hand, dietary yeast supplementation decreased serum triglyceride level in rams [8] .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Blood chemistry results and some hematological parameter results of present study had parallel with the of results Özsoy et al [7] that plasma cholesterol and triglyceride concentrations were not altered by yeast culture supplementation on goats and Yalçın et al [1] on dairy cows. On the other hand, dietary yeast supplementation decreased serum triglyceride level in rams [8] .…”
Section: Discussionsupporting
confidence: 79%
“…Studies on the effects of yeast cultures have reported variable results. These differences may depend on many factors such as diet composition, forage to concentrate ratio, type of forage feed, yeast dose, feeding strategy and stage of lactation [1] . Saccharomyces cerevisiae vary widely in efficiency, primarily because of differences in strain, the viability of yeast cells, and theirs dosage [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect of S. cerevisae on plasma levels of glucose, lactate, and urea-N is in agreement with the results of Stella et al (2007) and Yalçm et al (2011) in dairy goats and cows, respectively. Lascano et al (2012) observed that glucose concentrations tended to increase quadratically with increasing doses of S. cerevisae (S. cerevisiae CBS 493.94; 1 x 10 10 to 5 x 10 10 cfu/d) in dairy heifers fed low starch diets (16.7% of DM).…”
Section: Discussionsupporting
confidence: 78%
“…This finding could be a beneficial effect to dairy goat with high concentrate so that it will improve low fat milk that used to be with this level of concentrate. The 5 g yeast diet (PDY) contained more than twice higher in NDF and ADF than that of diet with 50 g Rumisacc, according to Yalçın et al (2011). Saccharomyces cereviseae populations in diets with yeast (PDY) and mix diet (PDM) were higher than other diets; however, curcuma in the mix diet affected the population by lowering it.…”
Section: Diets Chemical Compositionmentioning
confidence: 99%